Respon Publik Terhadap Pembatasan Pelaksanaan Walimatul ‘Ursy Selama PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat) Perspektif Maqashid Syari’ah - Zainal Hasan, Muhamad Fajar; Ulum, Fathul (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2022)
Walimatul „ursy is a wedding banquet. Islam requires to announce that the marriage contract has been completed, this is to distinguish it from secret marriages which are prohibited by Islam. However, currently the implementation of Walimatul „ursy has undergone changes due to the PPKM (Implementation of Community Activity Restrictions) policy after the Covid-19 pandemic, especially in Bago village itself. Therefore, the author wants to investigate further about the Public Response to Restrictions on the Implementation of Walimatul „ursy During Ppkm (Enforcement of Restrictions on Community Activities) from the Maqashid Syari'ah Perspective (Case Study in Bago Village, Pasirian District, Lumajang Regency). There are two problem formulations in this thesis, namely: (1) How is the response of the Bago village community, Kec. Pasirian Kab. Lumajang against restrictions on the implementation of walimatul „ursy during PPKM? (2) How is the application of restrictions on the implementation of walimatul „ursy during PPKM from a maqashid shari'ah perspective? The location of this research is in Bago Village, Pasirian District, Lumajang Regency, which is the reason the author chose this location, because this happened several community violations regarding the limitation of the implementation of walimatul „ursy during PPKM and can be reached by the author. This thesis uses a field research method, namely by going directly to the field/research location. Data collection techniques with interviews, and documentation. The data from this study consisted of primary data and secondary data which were then analyzed using qualitative descriptive analysis methods. From the research results obtained in the field, it can be concluded that the public response to restrictions on the implementation of walimatul „ursy during PPKM (implementation of restrictions on community activities) in Bago village is not effective, many people do not follow the protocol when attending the walimatul „ursy event, people have several reasons for The violations committed include: feeling safe because it is far from the city center, more concerned with tradition, and less firm action from the government. Maqashid Syariah‟s view of limiting the implementation of walimatul „ursy during PPKM (Enforcement of Restrictions on Community Activities) has 3 objectives, namely hifz an- nafs (guarding the soul), hifz an-nasl (guarding offspring), and hifz al-'aqli (guarding reason).